Miejsce kultury w niemieckich debatach wokół integracji imigrantów - Tomczak, Maria (Studia Europaea Gnesnensia, 2022)
The paper outlines major German experiences that the influx of migrants entailed. Against this background, the author examines the public debate surrounding the issue. The chief notions which inform it include multiculturalism (Multikultur), parallel societies (Parallelgesellschaften ), leading culture (Leitkultur) and welcoming culture (Willkommenskultur). Their very wording is indicative of how important cultural issues are. Indeed, the concern with potential threats to German culture have been a principal theme of the debates. Other aspects, such as the impact on the economy, society, or security tend to be overlooked or treated marginally. This fairly unusual approach to migration problems should be attributed to the characteristics of the German nation, for which culture is a principal mainstay. After all, the Kulturnation was constructed around culture as a unifying element and has become the foremost component in German self-awareness. Conse- quently, the influx of people representing other cultures engenders deeper insecurity and greater fears about the future than elsewhere.